Amplitude analysis and branching fraction measurement of the decay D s + $$ D_{s}^{+} $$ → K+ π + π − π 0 - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; M. Albrecht; R. Aliberti; A. Amoroso; M. R. An; Q. An; X. H. Bai; Y. Bai; O. Bakina; et al. (Journal of High Energy Physics, 2022)
Abstract The singly Cabibbo-suppressed decay D s + $$ D_s^{+} $$ → K + π + π − π 0 is observed by using a data set corresponding to an integrated luminosity of 6.32 fb −1 recorded by the BESIII detector at the centre-of-mass energies between 4.178 and 4.226 GeV. The first amplitude analysis of D s + $$ D_s^{+} $$ → K + π + π − π 0 reveals the sub-structures in this decay and determines the fractions and relative phases of different intermediate processes. The dominant intermediate process is D s + $$ D_s^{+} $$ → K *0 ρ +, with a fit fraction of (40.5 ± 2.8stat. ± 1.5syst. )%. With the detection efficiency based on our amplitude analysis, the absolute branching fraction for D s + $$ D_s^{+} $$ → K + π + π − π 0 is measured to be (9.75 ± 0.54stat. ± 0.17syst. ) × 10 −3.